An investigation of the nonlinear dynamic response of a flexible pipe undergoing vortex-induced vibrations and conveying internal fluid with variable-density. (1st July 2019) - Xie, Wude; Gao, Xifeng; Wang, Enhao; Xu, Wanhai; Bai, Yuchuan
Abstract: In this paper, a flexible pipe conveying variable-density fluid and simultaneously undergoing vortex-induced vibrations (VIV) is mathematically simulated and analysed. Resulting from multi-phase flows, the total fluid density inside the pipe may fluctuate temporally and spatially. This variable-density fluid is simulated with a mathematical model which obeys the conservation law of fluid mass. For the external VIV, the lift force caused by vortices shedding is modelled with a classic van der Pol wake oscillator. Based on the principle of Hamilton, the governing equations for the vibration of the pipe are derived. When only considering the fluctuation of the internal fluid density, the pipe is parametrically excited. The parametric resonances are determined with the Floquet theory. After this, the external VIV is taken into account and the influence from the internal varying fluid density on the VIV of the pipe is analysed in detail. When the internal fluid density fluctuates with different circular frequency, the vibrations of the pipe would become non-uniform or aperiodic. The root mean square displacement would increase or decrease. With the increase of the fluctuation amplitude of the internal fluid density, these phenomena would become more obvious. Nevertheless, the initial phase angle of the internal fluid density standing for the initial condition has seldom effect on the VIV of the pipe. Highlights: A theoretical model for a flexible pipe conveying variable-density fluid and simultaneously experiencing VIV was built. The parametric resonances of the pipe only induced by the variation of the internal fluid density were identified. The influence of the internal variable-density fluid on the pipe and on the VIV of the pipe was investigated.